Cultures of Image Construction. Approaching Planning Cultures as a Factor in Urban Image Production - Johannes Suitner (European Spatial Research and Policy, 2014)
Why do the same planning approaches cause different results around the world? Because, even in times of globalization, there is obviously more than one way of planning. These different modes are an expression of distinct local planning cultures. Hence, we need to take a closer look at the influence of planning cultures on outcomes of urban development processes. This paper joins debates on the nature of planning culture with culture-led image production as one specific process of urban development, and asks to what degree a local planning culture might influence the production of cultural image. The paper provides a first step in building an analytical framework for analyzing image production and its interplay with local planning cultures, and gives hints on critical points in the so-called ‘cultures of image construction’.